2020
DOI: 10.1038/s41598-020-74707-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low back pain and its remission on motor abundance in a low-load lifting task

Abstract: Having an abundance of motor solutions during movement may be advantageous for the health of musculoskeletal tissues, given greater load distribution between tissues. The aim of the present study was to understand whether motor abundance differs between people with and without low back pain (LBP) during a low-load lifting task. Motion capture with electromyography (EMG) assessment of 15 muscles was performed on 48 participants [healthy control (con) = 16, remission LBP (rLBP) = 16, current LBP (cLBP) = 16], du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…However, this excessive activation of trunk muscles would increase the spinal load and may contribute to the persistence of LBP [ 67 ]. This is in the line with a previous study investigating the muscle synergies during a lifting task in the CLBP group [ 68 ]. The study showed increased activations of synergies with back muscle coactivation patterns, which is considered as protective behaviors in individuals with CLBP [ 68 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, this excessive activation of trunk muscles would increase the spinal load and may contribute to the persistence of LBP [ 67 ]. This is in the line with a previous study investigating the muscle synergies during a lifting task in the CLBP group [ 68 ]. The study showed increased activations of synergies with back muscle coactivation patterns, which is considered as protective behaviors in individuals with CLBP [ 68 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, one study assessed the onset delay of transversus abdominis during rapid arm movements and subgroups of participants who resolved and not resolved from the adaptations identified while in pain were observed. 58,59…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, muscle synergies explaining most of the activation variance in healthy people were mainly represented by lumbar muscles, whereas the activation variance in individuals with clinical LBP was mainly explained by the activation of leg and thoracic muscles. In other words, people with clinical LBP relied more on leg and more global muscle strategies during lifting, 58 reaching, 98 and prone hip extension. 90 In one study of this review, muscle synergies related to lower limb actions were unaffected by pain during walking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in spinal pain disorders has evolved to encompass a breadth of scientific disciplines, varying from basic science (Falla et al , 2004, Hodges et al , 1999 to epidemiological research (Saragiotto et al , 2016a). Basic science investigations have ranged from studying individual muscle activity (Falla, Jull, 2004, Hodges, Cresswell, 1999, multimuscle synergies (Gizzi et al , 2015, Liew et al , 2020a, Liew et al , 2018, motor-unit (Falla et al , 2010, Yang et al , 2016a, spinal (Yu et al , 2017) and supraspinal activation (Hodges et al , 2009, Jacobs et al , 2010, Tsao et al , 2008. Epidemiological research has also encompassed a wide range of methodologies from cross-sectional diagnostic (Kim et al , 2018), longitudinal prognostic (Costa, Maher, 2012), longitudinal trajectory analysis (Kongsted et al , 2016), randomized controlled clinical trials (Griffin et al , 2017, Marin et al , 2017, Saragiotto et al , 2016b, stratified care (Foster, Hill, 2013, Kent et al , 2010, and causal mediation analysis (Lee et al , 2015).…”
Section: The Burden Of Musculoskeletal Spinal Painmentioning
confidence: 99%